Aim2 Couples With Ube2i for Sumoylation‐Mediated Repression of Interferon Signatures in Systemic Lupus Erythematosus. Issue 8 (7th July 2021) - Lu, Ailing; Wu, Shuxian; Niu, Junling; Cui, Mengmeng; Chen, Mengdan; Clapp, William L.; Barnes, Betsy J.; Meng, Guangxun
Abstract : Objective: Systemic lupus erythematosus (SLE) involves kidney damage, and the inflammasome‐caspase‐1 axis has been demonstrated to promote renal pathogenesis. The present study was designed to explore the function of the Absent in Melanoma 2 (Aim2) protein in SLE. Methods: Female wild‐type Aim2 −/−, Aim2 −/− Ifnar1 −/−, Aim2 −/− Rag1 −/−, and Asc −/− mice ages 8–10 weeks received 1 intraperitoneal injection of 500 μl pristane or saline, and survival of mice was monitored twice a week for 6 months. Results: The absence of Aim2, but not Asc, led to enhanced SLE in mice that received pristane treatment. Increased immune cell infiltration and type I interferon (IFN) signatures in the kidneys of Aim2 −/− mice coincided with severity of lupus, which was alleviated by blockade of Ifnar1 ‐mediated signal. Adaptive immune cells were also involved in the glomerular lesions of Aim2 −/− mice after pristane challenge. Importantly, even in the absence of pristane, plasmacytoid dendritic cells in the kidneys of Aim2 −/− mice were significantly increased compared to control animals. Accordingly, transcriptome analysis revealed that Aim2 deficiency led to enhanced expression of type I IFN–induced genes in the kidneys even at an early developmental stage. Mechanistically, Aim2 bound ubiquitin‐conjugating enzyme 2i (Ube2i), which mediates sumoylation‐based suppression of type I IFN expression deficiency of Aim2 decreased cellular sumoylation, resulting in an augmented type I IFN signature and kidney pathogenesis. Conclusion: The present study demonstrates a critical role for Aim2 in an optimal Ube2i ‐mediated sumoylation‐based suppression of type I IFN generation and development of SLE. As such, the Aim2 – Ube2i axis can thus be a novel target for intervention in SLE.